2022
DOI: 10.1016/j.jaad.2021.09.073
|View full text |Cite
|
Sign up to set email alerts
|

Gender trends in research output among matched dermatology residency applicants

Abstract: Gender trends in research output among matched dermatology residency applicantsTo the Editor: We enjoyed reading the article by Guo and Nambudiri 1 on gender differences in research output among dermatology residents, in which they demonstrated that men published on average 1 additional article during dermatology residency than women. In reply, Militello et al 2 provided an excellent complementary analysis of gender differences in research output among medical students, finding that female medical students pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Similarly, a 2019-2020 article from the Journal of the American Academy of Dermatology showcased that 51% of matched dermatology applicants were female authors [ 7 ]. The British Medical Journal also reported on the evolving gender trends in oncology research, noting a jump from 26.6% female authors in 2002 to 32.9% in 2019 [ 8 ]. Further emphasizing this pattern, a Journal of Nephrology publication revealed that first authorship by women in major US nephrology journals increased from 32% in 2011 to 40% in 2019 [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…Similarly, a 2019-2020 article from the Journal of the American Academy of Dermatology showcased that 51% of matched dermatology applicants were female authors [ 7 ]. The British Medical Journal also reported on the evolving gender trends in oncology research, noting a jump from 26.6% female authors in 2002 to 32.9% in 2019 [ 8 ]. Further emphasizing this pattern, a Journal of Nephrology publication revealed that first authorship by women in major US nephrology journals increased from 32% in 2011 to 40% in 2019 [ 9 ].…”
Section: Reviewmentioning
confidence: 99%
“…To the Editor: We thoroughly enjoyed reading the study by Zheng et al 1 on the analysis of research output among successfully matched dermatology applicants. Their work joins a growing body of literature examining differences in scholarly activities among dermatology trainees.…”
mentioning
confidence: 99%